2021
DOI: 10.3390/cells10030484
|View full text |Cite
|
Sign up to set email alerts
|

The Many Facets of Therapy Resistance and Tumor Recurrence in Glioblastoma

Abstract: Glioblastoma (GBM) is the most lethal type of primary brain cancer. Standard care using chemo- and radio-therapy modestly increases the overall survival of patients; however, recurrence is inevitable, due to treatment resistance and lack of response to targeted therapies. GBM therapy resistance has been attributed to several extrinsic and intrinsic factors which affect the dynamics of tumor evolution and physiology thus creating clinical challenges. Tumor-intrinsic factors such as tumor heterogeneity, hypermut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 155 publications
(194 reference statements)
0
72
0
1
Order By: Relevance
“…GBM is a highly malignant neoplasia, in which GBM angiogenesis and chemotherapy may be conditioned by multiple factors, including tumor location and natural substances [53][54][55]. In addition, GBM is difficult to treat effectively for lengthy survival, with many facets of therapy resistance and tumor recurrence [56][57][58]. Among these difficulties is the resistance to antiangiogenic therapy, in which the switch from sprouting to intussusceptive angiogenesis has been described as an escape mechanism [59].…”
Section: Discussionmentioning
confidence: 99%
“…GBM is a highly malignant neoplasia, in which GBM angiogenesis and chemotherapy may be conditioned by multiple factors, including tumor location and natural substances [53][54][55]. In addition, GBM is difficult to treat effectively for lengthy survival, with many facets of therapy resistance and tumor recurrence [56][57][58]. Among these difficulties is the resistance to antiangiogenic therapy, in which the switch from sprouting to intussusceptive angiogenesis has been described as an escape mechanism [59].…”
Section: Discussionmentioning
confidence: 99%
“…Following an 11-day protocol, CT-2A NS were generated in serum-free Dulbecco's Modified Eagle Medium / Nutrient Mixture F-12 (DMEM/F-12, Sigma-Aldrich) supplemented with epidermal growth factor (EGF, Thermofisher), fibroblast growth factor (FGF, Thermofisher) and B27 supplement (Thermofisher). After enzymatical dissociation (Stempro Accutase, Thermofisher), 1x10 4 NS-derived CT-2A cells were stereotactically inoculated in the right brain hemisphere of female, 12-14 week old C57BL/6 mice (Envigo), 2.5 mm lateral from the midline, 0.5 mm anterior to the bregma and 2.5 mm below the dura mater. During the whole procedure, the mice were kept under general anesthesia with an IP injection of 6μl/g body weight of a mixture of 18.75mg/ml ketamine (Pfizer) and 0.125% xylazine hydrochloride (Bayer).…”
Section: Methodsmentioning
confidence: 99%
“…. However, the tumor almost invariably develops resistance mechanisms leading to the onset of recurrences with a median progression free survival (PFS) of seven months [3,4]. At this stage, none of the available therapeutic options is truly effective, leading to a median overall survival (OS) of GBM patients of 14 months [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…Yet, if the bloodbrain barrier is not violated, the infiltration of peripheral immune cells into a tumor is limited. If the BBB is disrupted by tumor proliferation or inflammation, then the tumor can be infiltrated by immunosuppressive immune cells [67]. It has been shown that an immunosuppressive microenvironment in a glioma is created by immunosuppressive cytokines and chemokines (transforming growth factor beta (TGF-β), interleukin 10 (IL-10), prostaglandin E2) and immune cells (immunosuppressive natural killer T cells (NKT), T/B regulatory cells (T/Breg), tumor-associated macrophages (TAM)/microglia and myeloidderived suppressor cells (MDSC)).…”
Section: Immune Evasionmentioning
confidence: 99%